Simultaneous Determination of Active Clinical Components of Teicoplanin and Ramoplanin in Environmental Water by LC-MS/MS Coupled With Cascade Elution - Jin, Hui; Zhao, Cheng; Yin, Yi; Zheng, Guangming; li, Lichun; Shan, Qi; Zhang, Meiyu; Wei, Linting; Shi, Xiaona; Huang, Heqing; Zhang, Wenjing; Liu, Shugui (Frontiers in Environmental Science, 2021)
A simple, sensitive and simultaneous method was established and validated for active clinical components of teicoplanin and ramoplanin in environmental water by LC-MS/MS coupled with cascade elution. Moreover, a cascade elution method, which was rapid, solvent-less and high-extraction efficient, was successfully proposed to realize the extraction and purification of seven targets in one-step. Under the optimized conditions, the method showed excellent linearity with correlation coefficient (R2) ≥0.998 in the range of 1.0 ng L-1 to 100.0 ng L-1. Low matrix effects and good recoveries which ranged from 86 to 114% were reached with RSDs lower than 3.0% for most targets. The limits of detection and limit of quantification were 0.1-1.3 ng L-1 and 0.3-4.0 ng L-1, respectively. This method was successfully applied for the determination of teicoplanin and ramoplanin in water samples from the Pearl River and the South China Sea. TA2-2,3 was quantified in only one sample with the concentration of 8.0 ng L-1.